Literature Study: Stress Management in Social Entrepreneurs during the Covid-19 Pandemic - Hasnaa’ Zahuna Nayu; Sifa Afifah; Widya Maharani; Shallza Milinia Al Qisty; Aftina Nurul Husna (Urecol Journal. Part H: Social, Art, and Humanities, 2021)
The government made policies, namely learning from home, working from home, and worshiping at home, and implementing social distancing to reduce the spread of Covid-19. This was done because the cases experienced in Indonesia, especially continued to increase, even though for a while in several places there was a lockdown and PSBB (Large-Scale Social Restrictions), for example in DKI Jakarta and the Regional Government of Central Java had made a policy on February 6-7 to stay in home alone. The Covid-19 pandemic has an impact on almost all aspects of life. The stress experienced by workers will affect their emotions, thought processes, and their physical condition. The factors that trigger stress at work are the uncertainty of the situation when the pandemic ends, economic problems, salary cuts, or layoffs. The purpose of this study is to gather information through literature studies related to stress management in social entrepreneurs during the pandemic. This research method uses a systematic literature review by summarizing the results of previous studies. The results of the literature review conducted show that social entrepreneurship adheres more to social values and social welfare, where this arises because of a greater desire to help the community's economy, so that volunteerism to achieve goals can be used as coping stress to manage stress.